2012
DOI: 10.1093/ejcts/ezs512
|View full text |Cite
|
Sign up to set email alerts
|

Mesh–bone cement sandwich for sternal and sternoclavicular joint reconstruction

Abstract: Resection of the manubrium including both sternoclavicular joints is occasionally performed in the case of sternal tumours. Sternoclavicular joints are the only true joints connecting the axial skeleton to the upper extremity. Therefore, they play an important role in shoulder function. However, data on their reconstruction are lacking. Here, we described the case of a sternal reconstruction including both sternoclavicular joints using a mesh-bone cement sandwich. The mechanical properties of the construct mim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…To date, methods to reconstruct the chest wall, including the pleura and muscular layers, have involved using synthetic materials and covering them with autologous flaps if needed [3][4][5]. Rigid prostheses have also been used for the reconstruction of defects of the rib cage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, methods to reconstruct the chest wall, including the pleura and muscular layers, have involved using synthetic materials and covering them with autologous flaps if needed [3][4][5]. Rigid prostheses have also been used for the reconstruction of defects of the rib cage.…”
Section: Discussionmentioning
confidence: 99%
“…Various prosthetic materials have been used for reconstruction. There are methods to reconstruct pleura and soft tissue using synthetic materials such as polypropylene and polyester [ 3 ] and to perform rigid fixation in skeletal reconstruction by sandwiching bone cement between these materials [ 4 , 5 ]. However, these methods have major disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective study from the Mayo Clinic reported a 10-year disease-free survival of 95.4% with wider excision versus 65.4% with local excision, and a 52.1% recurrence rate in the latter group. 5 The important prognostic factors for long-term survival are tumor diameter, location, histopathologic grading, and complete excision with wide margins.…”
Section: Discussionmentioning
confidence: 99%
“…From these first prostheses many other different techniques have been proposed for rigid chest wall reconstruction with variable results such as the use of other mesh-bone cement sandwiches ( 66 ), Kirschner wires ( 67 ), steel sutures ( 68 ), ceratite prosthesis ( 69 ), porous alumina ( 70 ), Ley prosthesis ( 71 ), rib-like technique ( 72 ) or customized sternal plates ( 73 , 74 ) but titanium-based devices are by far the most commonly used nowadays. They have clear advantages over other systems (biocompatibility, osseointegration, resistance to infection, a high strength/weight ratio and low optical density), although they are not free of complications similar to other devices such as rupture, displacement, thoracic pain or infection ( 47 , 50 ).…”
Section: Reconstruction Techniquesmentioning
confidence: 99%